Research projects in innovation, technology and scientific dissemination in Latin American universities - Rincón Soto, Idana Beroska; Campos Díaz, Ángel Hugo; Villanueva Cadenas, Gladys Jane; Caro Soto, Félix Gil; Villanueva Cadenas, Dalila Irene (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The article is based on two central concepts, the first focuses on education and the second on human rights. The importance of starting from these concepts is due to the fact that each person has the right to receive quality education based on human rights, where each subject can enjoy a protected, inclusive and free life. It is essential to analyze the practice of education from a perspective based on human rights directly linked to social inclusion, in addition to the possibility of making proposals that help and frame this type of contribution to the exercise of human rights in education. Education based on human rights provides different spaces of action where a political-pedagogical activity interacts with the purpose of building in the classroom aspects that provide better inclusion and social equity for all. Education must be guaranteed by the States because access to it is a right for all individuals and starting from an approach towards the exercise of a human right is to think that it can be an engine to form the subjects on these bases and that truly any person can exercise it freely. Education has always had a fundamental role in the development and changes in different societies, these changes have been able to be made within and from human rights could not only be a challenge, but would bring immediate improvements in the quality of the subjects individually and collectively.